Method for preparing 99.99% quartz sand by taking river yellow sand as raw material

Through a combination of physics and chemistry, 99.99% high-purity quartz sand was prepared, which solved the problem of low resource utilization efficiency of river yellow sand, expanded the industrial use of quartz sand and improved economic benefits.

CN119430193AActive Publication Date: 2025-02-14JIANGSU YUANSHAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411511416.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-14
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize river yellow sand resources, especially to improve the purity of quartz sand and expand its industrial uses.

Method used

Using a combination of physical and chemical methods, including sand making and pretreatment, pickling, roasting and re-pickling, we remove impurities in the yellow sand of the river and improve the purity of quartz sand to 99.99%.

Benefits of technology

The production of high-purity quartz sand has been achieved, and its industrial uses have been expanded, including photovoltaic ultra-white glass, artificial quartz stone slab sand, etc., and the economic benefits of resources have been improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for preparing 99.99% quartz sand by taking river yellow sand as a raw material, which comprises the following steps: firstly, carrying out sand making and pretreatment on the river yellow sand raw material to ensure that SiO2 in the treated quartz raw material is greater than or equal to 99%; carrying out first pickling on the obtained quartz raw material, wherein a pickling solution is a composite acid solution composed of HF and ferrate; mixing the obtained quartz raw material with charcoal powder, preserving heat and roasting for 30-45 minutes under the condition of 1000 + / -50 DEG C, and cooling after roasting is finished; the obtained quartz raw material is subjected to acid pickling for the second time, the acid pickling solution is a composite acid solution composed of hydrochloric acid and EDTA, after acid pickling is completed, water washing and drying are conducted, and the quartz sand with the SiO2 purity not lower than 99.99% is obtained. According to the method, the high-purity quartz sand with the purity of 99.99% can be extracted from the river yellow sand with the low quartz content, the process is simple, and a high-temperature chlorination process is not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing 99.99% quartz sand by taking river yellow sand as raw material, belonging to the technical field of deep processing of non-metallic minerals. Background Art

[0002] At present, most of the high-purity quartz sand products with a purity of 99.99% or above are made of high-quality vein quartz ore, high-purity quartzite, and pebbles with high silica content. Some are made of granite pegmatite. With years of mining, high-grade quartz resources are becoming less and less. Therefore, it is imperative to expand the raw materials of high-purity quartz. my country's river sand resources are rich, but the quartz content of river sand is relatively low. It is mainly composed of a small amount of quartz and a large amount of feldspar. The quartz content is generally less than 50%, and the feldspar (including potassium feldspar, sodium feldspar, plagioclase, etc.) has a high content of metal components, including a large amount of Al 3+ 、Ti 4+ Impurity ions and Si in the quartz lattice 4+ 、Al 3+ The ions have similar ionic radii and are difficult to separate by physical methods.

[0003] The yellow sand and other sand and stone resources in the river are rich, which is one of the important siliceous raw material resources. The silicon dioxide content in high-quality yellow sand can reach about 70%, and other impurities include a small amount of soil, feldspar, magnetite, ilmenite, limonite, mica flakes, etc. It is a natural high-quality silica sand resource. If the river sand is not comprehensively processed and utilized, it will be deposited in the riverbed year after year, which will raise the riverbed and water level, and will bring floods to the people on both sides of the riverbed in the rainy season. At present, the yellow sand in the river is mostly used as cement concrete, cement floor, cement brick, lime sand brick, cement pole and other cement products, and a small amount is used as pesticide granules and casting sand materials. The economic value of the yellow sand is relatively low. How to scientifically and rationally develop the yellow sand resources in these rivers, so as to not only dredge the river to prevent floods, but also process and utilize them to improve their economic benefits, is of particular significance.

[0004] Patent CN1111097C discloses a method for purifying quartz sand from river silt. The method comprises seven process steps, namely, slurry screening, weak magnetic primary selection, heavy sand sorting, cylinder slag removal, strong magnetic sorting, light yarn sorting and coarse product selection, to obtain quartz sand with SiO2≥98%. However, the method cannot fundamentally solve the problem of separation of mica and feldspar, and the use of its product quartz sand is greatly limited; and the feldspar sand and iron ore contained in the yellow sand are not further recycled, but used as by-products for construction raw materials, which does not maximize the utilization value and the best economic benefits of the yellow sand. Patent CN103372496A discloses a process for separating quartz sand, feldspar sand and iron powder from river yellow sand. Although the above problems are solved, the quality standard requirements of less than 0.008% of ferric oxide in the quartz sand and less than 0.02% of ferric oxide in the feldspar sand after separation and the quality standard requirements of artificial quartz stone plate sand are still not solved. Therefore, scientifically and rationally developing and utilizing the cheap yellow sand resources in the river to maximize its utilization value and optimize its economic benefits has become one of the important topics for technicians in the field of siliceous material technology. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing 99.99% quartz sand by using cheap river yellow sand as raw material.

[0006] The solution adopted by the present invention to solve the above technical problems is:

[0007] A method for preparing 99.99% quartz sand using river yellow sand as raw material comprises the following steps:

[0008] (1) Sand making and pretreatment of river sand raw materials;

[0009] (2) subjecting the quartz raw material obtained in step (1) to a first pickling, wherein the pickling solution is a composite acid solution composed of HF and ferrate;

[0010] (3) mixing the quartz raw material obtained in step (2) with carbon powder, calcining at 1000±50°C for 30-45 minutes, and cooling after calcination;

[0011] (4) The obtained quartz raw material is subjected to a second pickling, wherein the pickling solution is a composite acid solution composed of a halogen acid and a heavy metal complexing agent. After the pickling is completed, the quartz raw material is washed with water and dried to obtain quartz sand with a SiO2 purity of not less than 99.99%.

[0012] Furthermore, the pretreatment process in step (1) is selected from one or both of magnetic separation and flotation. The purpose of pretreatment is mainly to remove aluminum silicate minerals such as feldspar and impurities such as pyrite in the river sand raw material.

[0013] Furthermore, the pretreatment process in step (1) includes at least one magnetic separation and at least one flotation.

[0014] Furthermore, the magnetic separation adopts electromagnetic separation with a magnetic field strength of 13000 to 18000 Gauss.

[0015] Furthermore, the flotation is carried out with HF as an activator and regulator, dodecylamine as a collector, and pH = 2.0-2.5. Feldspar and other aluminum silicate impurities and other organic impurities are floated out with the foam.

[0016] Furthermore, the quartz sand obtained after each flotation is subjected to X-ray phase analysis, and the flotation is stopped when the feldspar content in the quartz sand is less than 1%.

[0017] Furthermore, step (1) adopts grinding to make sand. For example, grinding by rod mill. The grinding process allows the quartz and other minerals in the coarse-grained river yellow sand to be fully dissociated. After the sand is dissociated, it is classified and the part with a particle size range of 60-150 mesh is selected as the quartz raw material for the next step.

[0018] Furthermore, SiO2 in the quartz raw material after pretreatment in step (1) is ≥99%.

[0019] Furthermore, the first pickling temperature is 80±5°C, and the pickling time is 3 to 4 hours; the second pickling temperature is 80±5°C, and the pickling time is 3 to 4 hours.

[0020] The first pickling is oxidative pickling, the purpose of which is to remove the residual aluminum silicate minerals and pyrite minerals in the quartz raw material, so that the SiO2 of the purified raw quartz sand is ≥99.9%. HF removes the residual aluminum silicate mineral impurities in the quartz sand, and the strong oxidizing property of sodium ferrate can oxidatively decompose the sulfide mineral impurities, which improves the whiteness of the quartz sand while improving the whiteness of the quartz sand, so that it meets the standard requirements for quartz sand used in artificial stone slabs.

[0021] Furthermore, in step (2), the quartz raw material is pickled with HF and ferrate, and then deacidified and washed with tap water until it becomes neutral.

[0022] Furthermore, the halogen acid in step (4) is hydrochloric acid, and the heavy metal complexing agent is EDTA.

[0023] Furthermore, after the acid washing in step (4), the product is deacidified, washed with tap water until neutral, washed with electronic grade pure water at least three times and then dried.

[0024] Furthermore, the mass fraction of HF in the composite acid solution used for the first pickling is 10% to 30%, and the mass fraction of ferrate is 0.001% to 1%, and more preferably 0.001% to 0.1%.

[0025] Furthermore, the ferrate is selected from sodium ferrate or potassium ferrate.

[0026] Furthermore, the mass fraction of the halogen acid in the composite acid solution used for the second pickling is 20% to 30%, and the mass fraction of the metal complexing agent is 0.01% to 0.05%.

[0027] Furthermore, in step (3), the material is cooled to the second pickling temperature or not higher than the second pickling temperature by no more than 25° C. For example, the second pickling temperature is 80±5° C., and in step (3), the material can be cooled to 95-105° C.

[0028] Furthermore, the carbon powder used in step (3) is selected from wood carbon powder, coke powder or activated carbon powder sold on the market.

[0029] Furthermore, the mass of the carbon powder used in step (3) is 0.5% to 2% of the mass of the quartz raw material, for example, 0.8% or 1%.

[0030] The purpose of high temperature calcination in step (3) is to remove gas-liquid inclusions in the quartz. The purpose of pickling in step (4) with a composite acid solution composed of a halogen acid and a heavy metal complexing agent can remove metal, alkali metal and alkaline earth metal impurities in the quartz raw material, so that the purity of the final product SiO2 is not less than 99.99% without the need for high temperature chlorination.

[0031] The present invention adopts a method combining physics and chemistry, with high impurity removal rate, low quartz sand loss rate, and less equipment investment, realizing product upgrading. The produced quartz sand has high purity, and can not only be used as raw material for photovoltaic ultra-white glass, but also can be used to prepare high value-added artificial quartz stone plate sand raw material, such as crystal glass, crystalline glass, high-grade ceramics, high-boron glass tube, silicon micropowder for electronic and electrical engineering, etc., and can also be used as sand for tap water filtration and artificial quartz plate, etc. The purity problem of quartz sand purified from river yellow sand is solved, and the industrial use of quartz sand purified from river yellow sand is greatly expanded. DETAILED DESCRIPTION

[0032] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0033] Example 1

[0034] Take the yellow sand in the river channel of Macheng City, Hubei Province as an example.

[0035] 1. Select coarse-grained (2-40 mesh) river sand as raw material and perform X-ray phase analysis. The analysis results show that the quartz content is 35%, and the rest are potassium feldspar, sodium feldspar and plagioclase minerals.

[0036] 2. Pretreatment of raw quartz sand:

[0037] a. Sand making + magnetic separation: Use rod mill for grinding, use 60-mesh drum screen as upper screen and 150-mesh drum screen as lower screen for wet classification, collect 60-150-mesh mortar, most of the 150-mesh sieve under the sieve is feldspar sand powder, which can be purified and used separately. The screened quartz raw materials are respectively de-ironized by 13,000 Gauss electromagnetic separation and 18,000 Gauss electromagnetic separation, and the de-ironized mortar is dehydrated for flotation;

[0038] b. Flotation: HF is used as an activator and pH adjuster, dodecylamine is used as a collector (dosage is 500 g / t), and flotation is carried out at pH = 2.0. The quartz sand obtained after each flotation is subjected to X-ray phase analysis. After 6 flotations, the feldspar mineral content in the quartz sand is less than 1%. Stop flotation, wash and dehydrate the quartz sand for later use.

[0039] 3. Pickling to remove aluminum silicate and pyrite impurities: The quartz sand after flotation is treated with a composite acid solution composed of 18% HF + 0.02% sodium ferrate at 80°C for 3 hours (reference patent for pickling equipment CN201110247061.4). After pickling, remove the acid solution, wash with clean tap water until neutral, and dehydrate for later use. Sample analysis shows that the SiO2 content in the raw quartz sand is 99.92%.

[0040] 4. Mix the raw quartz sand after the first pickling evenly with wood carbon powder accounting for 1% of the mass of the quartz sand, and roast it at 1050℃ for 30 minutes. After roasting, cool it to 95℃ for use.

[0041] 5. The quartz sand obtained in step 4 is pickled with a composite acid solution composed of 30% hydrochloric acid + 0.01% EDTA at 80°C for 3 hours. After pickling, the acid solution is removed, and the quartz sand is first washed with clean tap water until the washing water is neutral, and then washed three times with electronic grade pure water, and dehydrated for use.

[0042] 6. Send the material after the second pickling in step 5 to a high-temperature drying device for drying, and take samples of the dried quartz sand for analysis.

[0043] Sampling was performed according to the GB / T32649-2016 "High-purity quartz sand for photovoltaic use" standard, and the impurity elements in the obtained quartz sand product were detected according to the impurity element detection method in the "GB / T3284-2015 Quartz Glass Chemical Composition Analysis Method". The sampling and testing methods of all embodiments of this application are the same, and the above standards are adopted.

[0044] The test results of the quartz sand product obtained in this embodiment are: SiO2: 99.99%, aluminum: 22.3ppm, iron: 0.5ppm, potassium: 1.0ppm; sodium: 1.2ppm; calcium 0.9ppm:; magnesium: 0.8ppm; titanium: 2.4ppm.

[0045] The quartz glass tube drawn by high-temperature electric melting using this sand as raw material has a hydroxyl content of 5ppm according to GB / T1242-2019 "Test Method for Hydroxyl Content in Quartz Glass".

[0046] Comparative Example 1

[0047] The only difference from Example 1 is that the composite acid solution used in step 3 is 18% HF + 0.02% oxalic acid. After the first pickling, the sampling and analysis of the SiO2 content in the raw quartz sand is 99.8%. The final quartz sand product test results are: SiO2: 99.97%, aluminum: 37.8ppm, iron: 7.5ppm, potassium: 3.0ppm; sodium: 4.2ppm; calcium: 15.5ppm; magnesium: 0.8ppm; titanium: 6.4ppm.

[0048] Comparative Example 2

[0049] The difference from Example 1 is that the pickling solution used in step 5 is 30% hydrochloric acid, and the final quartz sand product test results are: SiO2: 99.98%, aluminum: 46.3ppm, iron: 3.5ppm, potassium: 4.8ppm; sodium: 6.1ppm; calcium 16.8.ppm:; magnesium: 1.8ppm; titanium: 8.5ppm.

[0050] Example 2

[0051] Take the yellow sand of Shangba River in Xishui County, Hubei Province as an example.

[0052] 1. Select coarse-grained (2-50 mesh) river sand as raw material and perform X-ray phase analysis. The analysis results show that the quartz content is 40%.

[0053] 2. Pretreatment of raw quartz sand:

[0054] a. Sand making + magnetic separation: Use rod mill for grinding, use 60 mesh drum screen as upper screen and 150 mesh drum screen as lower screen for wet classification, collect 60-150 mesh mortar. The screened quartz raw materials are respectively deironed by 13000 Gauss electromagnetic separation and 18000 Gauss electromagnetic separation, and the deironed mortar is dehydrated for flotation;

[0055] b. Flotation: HF is used as an activator and regulator, dodecylamine is used as a collector (500 g / t), and flotation is carried out at pH = 2.5. The quartz sand obtained after flotation is subjected to X-ray phase analysis each time. After 6 flotations, the feldspar content in the quartz sand is less than 1%. Stop flotation, wash and dehydrate the quartz sand for later use.

[0056] 3. Pickling to remove aluminum silicate and pyrite impurities: The quartz sand after flotation was subjected to dynamic pickling at 85°C for 4 hours with a composite acid solution consisting of 16% HF + 0.01% potassium ferrate. After pickling, the acid solution was removed and the sand was washed with clean tap water until neutral. After dehydration, it was set aside. The SiO2 content in the raw quartz sand was sampled and analyzed to be 99.93%.

[0057] 4. Mix the raw quartz sand after the first pickling evenly with 1% of the wood carbon powder by mass of the quartz sand, and roast it at 1000℃ for 45 minutes. After roasting, cool it to 105℃ for use.

[0058] 5. The quartz sand obtained in step 4 is pickled with a composite acid solution composed of 20% hydrochloric acid + 0.05% EDTA at 85°C for 3.5 hours. After pickling, the acid solution is removed, and the quartz sand is first washed with clean tap water until the washing water is neutral, and then washed three times with electronic grade pure water, and dehydrated for use.

[0059] 6. Send the material after the second pickling in step 5 to a high-temperature drying device for drying, and take samples of the dried quartz sand for analysis. Among them, SiO2: 99.99%, aluminum: 20.8ppm, iron: 0.6ppm, K: 1.1ppm; sodium: 1.3ppm; calcium: 0.8ppm; magnesium: 0.9ppm; titanium: 2.6ppm.

[0060] The quartz glass tube drawn by high-temperature electric melting using this sand as raw material has a hydroxyl content of 6ppm according to GB / T1242-2019 "Test Method for Hydroxyl Content in Quartz Glass".

[0061] Example 3

[0062] Take the yellow sand in the river channel in Hong’an County, Hubei Province as an example.

[0063] 1. Select coarse-grained (2-60 mesh) river sand as raw material and perform X-ray phase analysis. The phase analysis results show that the quartz content is 36%.

[0064] 2. Pretreatment of raw quartz sand:

[0065] a. Sand making + magnetic separation: Use rod mill for grinding, use 60 mesh drum screen as upper screen and 150 mesh drum screen as lower screen for wet classification, collect 60-150 mesh mortar. The screened quartz raw materials are respectively deironed by 13000 Gauss electromagnetic separation and 18000 Gauss electromagnetic separation, and the deironed mortar is dehydrated for flotation;

[0066] b. Flotation: HF is used as an activator and regulator, dodecylamine is used as a collector (800 g / t), and flotation is carried out at pH = 2.0. The quartz sand obtained after flotation is subjected to X-ray phase analysis each time. After 5 flotations, the feldspar content in the quartz sand is less than 1%. Stop flotation, wash and dehydrate the quartz sand for later use.

[0067] 3. Pickling to remove aluminum silicate and pyrite impurities: The quartz sand after flotation is treated with a composite acid solution composed of 16% HF + 0.01% sodium ferrate at 80°C for 4 hours. After the pickling, the acid solution is removed and washed with clean tap water until neutral. After dehydration, it is ready for use. The SiO2 content in the raw quartz sand is 99.93% after sampling and analysis.

[0068] 4. Mix the raw quartz sand after the first pickling evenly with 1% of the wood carbon powder by mass of the quartz sand, and roast it at 1000℃ for 45 minutes. After roasting, cool it to 105℃ for use.

[0069] 5. The quartz sand obtained in step 4 is pickled with a composite acid solution composed of 25% hydrochloric acid + 0.03% EDTA at 80°C for 3.5 hours. After pickling, the acid solution is removed, and the quartz sand is first washed with clean tap water until the washing water is neutral, and then washed three times with electronic grade pure water, and dehydrated for use.

[0070] 6. Send the material after the second pickling in step 5 to a high-temperature drying device for drying, and take samples of the dried quartz sand for analysis. Among them, SiO2: 99.99%, aluminum: 20.8ppm, iron: 0.6ppm, K: 1.1ppm; sodium: 1.3ppm; calcium: 0.8ppm; magnesium: 0.9ppm; titanium: 2.6ppm.

[0071] The quartz glass tube drawn by high-temperature electric melting using this sand as raw material has a hydroxyl content of 6ppm according to GB / T1242-2019 "Test Method for Hydroxyl Content in Quartz Glass".

[0072] Example 4

[0073] Take the yellow sand in the river channel of Luotian County, Hubei Province as an example.

[0074] 1. Select coarse-grained (2-30 mesh) river sand as raw material and perform X-ray phase analysis. The analysis results show that the quartz content is 45%.

[0075] 2. Pretreatment of raw quartz sand:

[0076] a. Sand making + magnetic separation: Use rod mill for grinding, use 60 mesh drum screen as upper screen and 150 mesh drum screen as lower screen for wet classification, collect 60-150 mesh mortar. The screened quartz raw materials are respectively deironed by 13000 Gauss electromagnetic separation and 18000 Gauss electromagnetic separation, and the deironed mortar is dehydrated for flotation;

[0077] b. Flotation: HF is used as an activator and regulator, dodecylamine is used as a collector (1000 g / t), and flotation is carried out at pH = 2.3. The quartz sand obtained after flotation is subjected to X-ray phase analysis each time. After 4 flotations, the feldspar content in the quartz sand is less than 1%. Stop flotation, wash and dehydrate the quartz sand for later use.

[0078] 3. Pickling to remove aluminum silicate and pyrite impurities: The quartz sand after flotation is treated with a composite acid solution composed of 20% HF + 0.02% sodium ferrate at 80°C for 3 hours. After the pickling, the acid solution is removed and washed with clean tap water until neutral. After dehydration, it is ready for use. The SiO2 content in the raw quartz sand is 99.94% after sampling and analysis.

[0079] 4. Mix the raw quartz sand after the first pickling evenly with 1.5% of wood carbon powder by mass of the quartz sand, and roast it at 1050℃ for 30 minutes. After roasting, cool it to 95℃ for use.

[0080] 5. The quartz sand obtained in step 4 is pickled with a composite acid solution composed of 28% hydrochloric acid + 0.02% EDTA at 80°C for 3 hours. After pickling, the acid solution is removed, and the quartz sand is first washed with clean tap water until the washing water is neutral, and then washed three times with electronic grade pure water, and dehydrated for use.

[0081] 6. Send the material after the second pickling in step 5 to a high-temperature drying device for drying, and take samples of the dried quartz sand for analysis. Among them, SiO2: 99.99%, aluminum: 20.3ppm, iron: 0.7ppm, K: 1.0ppm; sodium: 1.2ppm; calcium: 0.7ppm; magnesium: 0.5ppm; titanium: 2.2ppm.

[0082] The quartz glass tube drawn by high-temperature electric melting using this sand as raw material has a hydroxyl content of 5ppm according to GB / T1242-2019 "Test Method for Hydroxyl Content in Quartz Glass".

[0083] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A method for preparing 99.99% quartz sand using river sand as raw material, characterized in that: The steps include: (1) Sand making and pretreatment of river sand raw materials; (2) subjecting the quartz raw material obtained in step (1) to a first pickling, wherein the pickling solution is a composite acid solution composed of HF and ferrate; (3) mixing the quartz raw material obtained in step (2) with carbon powder, calcining at 1000±50°C for 30-45 minutes, and cooling after calcination; (4) The obtained quartz raw material is subjected to a second pickling, wherein the pickling solution is a composite acid solution composed of a halogen acid and a heavy metal complexing agent. After the pickling is completed, the quartz raw material is washed with water and dried to obtain quartz sand with a SiO2 purity of not less than 99.99%.

2. The method according to claim 1, characterized in that The pretreatment process in step (1) is selected from one or both of magnetic separation and flotation.

3. The method according to claim 1, characterized in that The particle size range of the quartz raw material obtained by sand making in step (1) is 60 to 150 meshes.

4. The method according to claim 1, characterized in that: The first pickling temperature is 80±5℃, and the pickling time is 3 to 4 hours; the second pickling temperature is 80±5℃, and the pickling time is 3 to 4 hours.

5. The method according to claim 1, characterized in that The mass fraction of HF in the composite acid solution used for the first pickling is 10% to 30%, and the mass fraction of ferrate is 0.001% to 0.1%.

6. The method according to claim 1, characterized in that The ferrate is selected from sodium ferrate or potassium ferrate.

7. The method according to claim 1, characterized in that The mass fraction of the halogen acid in the composite acid solution used for the second pickling is 20% to 30%, and the mass fraction of the metal complexing agent is 0.01% to 0.05%.

8. The method according to claim 1, characterized in that Step (3) cools the material to the second pickling temperature or to a temperature not more than 25° C. higher than the second pickling temperature.

9. The method according to claim 1, characterized in that: The SiO2 content of the quartz raw material obtained after the first pickling is ≥99.9%.

10. The method according to claim 1, characterized in that The mass of the carbon powder used in step (3) is 0.5% to 1% of the mass of the quartz raw material.

Citation Information

Patent Citations

  • High-purity quartz sand purifying and pickling device

    CN102303870A

  • Process method for separating quartz sand, arkosic sand and iron powder from river yellow sand

    CN103372496A

  • Method for obtg. quartz sands by dressing mud and sand deposited on river bed

    CN1111097C

  • Purification method of high-purity quartz sand with SiO2 purity more than or equal to 99.99%

    CN110127708A